Nodularization Effect Evaluationof Ductile Iron based on Quick Testing Oxygen Content in Liquid Iron - PEI Li-xin; XU Zhen-yu; LI Da-yong (Journal of Harbin University of Science and Technology)
In order to explore the evaluation method of nodularization effect in iron melting through oxygen content，the active oxygen content was tested on-line in the preparation of nodularized melting with different nodularizing status by oxygen concentration cell. The results showed that there was an obvious difference between oxygen activity αo and oxygen potential Eo in the characterization of oxygen content status in the iron melting. By thermodynamics and metallurgical theory analysis of the oxygen concentration cell and graphite spheroidization in iron melting，the testing temperature and oxygen balance status in the iron melting might be the main causes leading to the difference between αo and Eo. Accordingly，the disadvantage of single parameter method by αo to evaluation spheroidization rate was analyzed， and simultaneously the two-parameter method combined αo with Eo was investigated for nodularization evaluation. Finally，the metallurgical implications of the αo and Eo were further explained